Effectiveness of RME Model to Understand Mathematical Concepts Ability Based on Keirsey's Personality Type - Syita Fatih 'Adna; Yesi Franita; Ditaul Safitri (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study is to identify (1) effectiveness between the RME learning model and the direct learning on the ability to understand mathematical concepts, (2) the effect of different personality types on the ability to understand mathematical concepts (3) the interaction between learning models and personality types. to the ability to understand mathematical concepts. The design of this study used a quasi-experimental, namely the nonequivalent posttest-only control group. The population in study were all students of class VII SMP N 1 Magelang totaling 250 students. Sampling in study used the Cluster Random Sampling technique. Collecting data using a questionnaire and post-test. The data analysis technique in this study used a two-way analysis of variance with unequal cells, with the prerequisites of the analysis that normality was by the Liliefors test and homogeneity was by the Barlett test. Based on hypothesis testing, the results obtained are that (1) RME learning model is more efective than direct learning in the ability to understand mathematical concepts, (2) there is no effect of different personality types on the ability to understand mathematical concepts, (3) there is an interaction between the learning model and personality type. on the ability to understand mathematical concepts.